The Effect of Isotonic Training and Isometric Training on Upper Passing Ability in the Game of Volleyball - Hakim, Hikmad; Nawir, Nukhrawi (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine the effect of isotonic training and isometric training on the ability to pass the top in the game of volleyball. The population and sample are 60 students of SMA Negeri 5 Makassar. Sampling techniques in research based on clusters. The data analysis technique used is a t-test at a significant level of 95%. By looking at the existing problems, the results of the scores obtained from data processing showed that: There was a significant influence of passing practice on the reflection of the wall on the ability to pass the top in the ball game in students of SMA Negeri 5 Makassar (to = 11,635 > tt = 2,045). There was a significant effect of isometric training on the ability to pass the top in the game of volleyball in students of SMA Negeri 5 Makassar (to = 11.919 > tt = 2.045). There was a significant difference in the influence between isotonic training and isometric training on the ability to pass the top in the game of volleyball in students of SMA Negeri 5 Makassar (to = 10,145 > tt = 2,000).